Status of Refugees in Accordance with the International Law and Legislation of Kazakhstan - OMAROVA, Ayman B.; APAKHAYEV, Nurlan; KOISHYBAIULY, Kuanysh; TLEUOV, Tleubek; BURIBAYEV, Yermek A.; KHAMZINA, Zhanna A. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
This paper contains an attempt to study international legal framework of refugees’ status and the standards of the national legislation of Kazakhstan devoted to legal regulation of refugees’ position in an integrated manner. As a result of the study we analyzed the main stages of refugees’ problem genesis in legal aspect; comparing different approaches and points of view we revealed the data about definition of the ‘refugee’ concept and developed a new definition based on their analysis; here we also represented the analysis of the both basic and supplementary international legal sources in the sphere of protection of refugees’ rights; we conducted international legal analysis of activities of the international universal and regional bodies and organizations protecting refugees’ rights; we also revealed the main directions of the policy and the situation in Kazakhstan regarding refugees; we worked out a series of recommendations on improvement of the national legislation of Kazakhstan in the sphere of protection of refugees’ rights. It is stated that legal confirmation of the refugees’ status is usually of declarative nature, which is in its turn a direct consequence of lack of a proper attention to the mechanisms for implementation of refugees’ rights protection. It is also stated that efficiency of international legal regulation depends on the opportunities and ways of implementation of the international law standards in the national legal field. Thus, an elaborated well-adjusted mechanism for ensuring legal status of refugees should be efficiently applied towards them, their legal rights and freedoms should be observed and the measures for improvement of their position should be timely taken.